HUBUNGAN PENGETAHUAN, SIKAP, DAN PERILAKU MENYIKAT GIGI DENGAN INDEKS DMF-T SISWA KELAS 6 SDN HARAPAN BARU 03 KECAMATAN BEKASI UTARA - Muhammad Eger Pratama (2015)
The prevalence of childhood caries is increasing during the past two decades and Indonesia's DMF-T index is far from the target value although the impact is disastrous. Maintaining the oral health can prevent this problem. Brushing teeth is one of the oral health practice components. Recent studies that have been conducted are not specific in discussing about the relationship between brushing teeth knowledge, attitude, practice and DMF-T index. The aim of the study is to determine the relationships between brushing teeth knowledge, attitude, practice and Harapan Baru 03 Kecamatan Bekasi Utara 6 th Graders' DMF-T index. This is an analytical non-paired comparative study with cross sectional approach. There are 95 respondents whom are taken using simple random sampling method from the twelve-year-old 6 th graders. The result of bivariate analysis using chi-square shows that there are relationships between brushing teeth knowledge and DMF-T index (p=0,000), brushing teeth attitude and DMF-T index (p=0,000), brushing teeth practice and DMF-T index (p=0,000). The conclusion is there are relationships between brushing teeth knowledge, attitude, practice and DMF-T index.